¿QUIÉN MATÓ A AGUIRRE? ACERCA DE LA REPRESIÓN PERONISTA DURANTE LA HUELGA AZUCARERA DE 1949 - PILIPONSKY, ESTEBAN (Universidad Nacional del Litoral, 2015)
In 1949 it took place in Argentina, with its epicenter in Tucuman, the largest sugar strike in its history. It was severely attacked and repressed. Violence by the Peronist government was extended with special bitterness toward leftists. This attack involved from the expulsion of those from their positions in the unions, to imprisonment, kidnapping, torture, and murder of Antonio Aguirre, member of the Communist Party and member of the union of waiters in the province. This paper examines the circumstances in which the crime occurred, crucial for a proper understanding of the politics of the populist regime in connection with the labor and trade union movement.